ISLAMIC PARENTING PERSPEKTIF AL-QUR’AN DAN IMPLIKASINYA TERHADAP PEMBENTUKAN KARAKTER ANAK: Tadabbur QS. Luqman Ayat 13-14 - Pitri Khayrani (Sekolah Tinggi Ilmu Al-Qur'an Ar-Rahman, 2025)
Character education has become an urgent need in the education of Indonesian children. Various moral crises such as violence, drug abuse, and sexual harassment have weakened the nation's mentality. One relevant solution is the application of Islamic Parenting based on the values of the Qur'an. The research method used is a literature study with a ten-step tafsir (reflection) approach to the Qur'anic verses. This study aims to examine the concept of parenting in Surah Luqman verses 13-14 and its implications for shaping the Islamic character of Indonesian children. The findings indicate that these verses emphasize the importance of education on monotheism, gratitude towards Allah and parents, as well as other moral values. Luqman al-Hakim, as the wise father figure, sets an example through a dialogical and wise approach, which can be applied in modern child-rearing. Challenges such as the influence of global culture, lack of religious understanding, and busy parents can be overcome through the consistent instilling of Islamic values. Thus, the Islamic Parenting method based on Surah Luqman is capable of shaping a morally and ethically strong generation.